2016
DOI: 10.1039/c6cy01631f
|View full text |Cite|
|
Sign up to set email alerts
|

An adamantane-based COF: stability, adsorption capability, and behaviour as a catalyst and support for Pd and Au for the hydrogenation of nitrostyrene

Abstract: A bimodal (micro/mesoporous) COF was synthesized by coupling tetrakis-1,3,5,7-(4′-iodophenyl)adamantane with 4,4′-diethynylbiphenyl following a Sonogashira protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…They confirm the amorphous nature of the organic polymers (Figure a). The absence of reflection lines of copper species (POP1 support) and of palladium at 2θ 41° (POP2‐POP4 supports) indicates that the small loadings of the remnant Sonogashira catalyst exist only in a highly dispersed state . After the deposition‐precipitation of the noble metals (Figure b,c), the recorded patterns shown that Pt is deposited in a high dispersion (no line, even after the reduction, Figure b), while Pd agglomerated after the reduction in hydrogen (line at 2θ 41°, Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They confirm the amorphous nature of the organic polymers (Figure a). The absence of reflection lines of copper species (POP1 support) and of palladium at 2θ 41° (POP2‐POP4 supports) indicates that the small loadings of the remnant Sonogashira catalyst exist only in a highly dispersed state . After the deposition‐precipitation of the noble metals (Figure b,c), the recorded patterns shown that Pt is deposited in a high dispersion (no line, even after the reduction, Figure b), while Pd agglomerated after the reduction in hydrogen (line at 2θ 41°, Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The stirring was continued for another 2 h, and then the supported solid was washed with distilled water, dried at 80 °C for 2 h under vacuum and at 80 °C overnight. Finally, Pd/POP1‐4 and Pt/POP2 were reduced under a hydrogen flow (30 mL/min) at 200 °C for 3 h. The synthesis of the Pd/C based catalyst was described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] Especially in catalytic application, COFs are desirable candidate materials. Moreover,t he elegant p skeletons of 2D COFs provide a fundamental basis for structural design.…”
Section: Introductionmentioning
confidence: 99%